Arabic Speech Recognition and Artificial Intelligence Technologies - Seyidov, Rashad; Çitil, Ahmet (Journal of Ecohumanism, 2024)
This article presents a compilation on the use and impacts of artificial intelligence technologies in the Arab world. Artificial intelligence is bringing about significant changes in various sectors such as healthcare, education, transportation, agriculture, and energy. In the healthcare sector, artificial intelligence can improve the quality of healthcare services by aiding in disease diagnosis and treatment. In education, it can offer personalized learning experiences to students and enhance educational materials. In the transportation sector, artificial intelligence can reduce traffic congestion and enhance safety through autonomous vehicles and smart transportation systems. In agriculture, it can increase productivity and provide solutions to food security challenges. In the energy sector, artificial intelligence can enhance energy efficiency and promote the use of sustainable energy sources. The use of artificial intelligence technologies in the Arab world also poses some challenges. Ethical, social, and legal considerations may affect the societal acceptance and usage of these technologies. Changes in the labor market may also occur, necessitating adaptation. However, with appropriate policies and regulations, artificial intelligence technologies can accelerate the digital transformation of the Arab world and contribute to sustainable development.